ANALISIS KETERKAITAN SEKTOR PERTANIAN TERHADAP SEKTOR PEREKONOMIAN LAIN DALAM PEMBANGUNAN WILAYAH DI ERA OTONOMI DAERAH KABUPATEN KARANGANYAR - Ropingi, Ropingi; Agustono, Agustono; Tbjp, Catur (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2009)
In the era of regional autonomy, local government is given the autonomous determine the objectives based on the local potentials. The research aims to seek information of agriculture sector's role in the autonomy era in Karanganyar District with the following purposes: (l) to study the relations between the agriculture sector and other sectors; (2) to study the past relations between the agriculture sector and other sectors; (3) to discover if the agriculture sector is the leading sector in Karanganyar. The result show that: I ) in 2005, Fisheries, forestry, animal husbandry, and estate crops are the Agriculture sub-sectors utilizing outputs from other economy sectors, while food crops utilizes the least; 2) all sub sectors have low future dependencies, meaning that only relatively low agriculture outputs are used as production inputs in other sectors; (3) agriculture sub-sectors that are key in utilizing other sector's output, including forest animal husbandry, and estate crop subsectors; (4) All Agriculture sub-sectors in Karanganyar in 2005 has the sensitivity value less than one, in other words Agriculture sub-sectors are not the significant in boosting the development of other sectors.